CHANGES OF 1ST GRADE SCHOOL CHILDREN’S EMOTIONAL AND SOCIAL COMPETENCES IN TANZPRO-BIODANZA INTERVENTION GROUP - Greaves, Vineta; Stueck, Marcus; Svence, Guna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The aim of this study is to investigate changes of 1st grade school children’s (age 6 -7) emotional and social competences in TANZPRO-Biodanza intervention group. In total 22 sessions were carried out during the school year 2014 / 2015 - from the beginning of October, 2014 until the end of May, 2015. The Emotion Questionnaire (Rydell et al., 2003) parents’ version was used to evaluate emotional competence – emotionality and emotion regulation. Prosocial scale, Internalizing and Externalizing scale of The Strengths and Difficulties Questionnaire (SDQ, Goodman,1997) parents‘ versions were used to measure social competence, i.e., prosocial behaviour and nonexistence of behavioural problems. Testing was performed in 3 time points – before intervention, after 10 sessions, and after intervention. Pre and post intervention results of social and emotional competence revealed different changes of experimental (n = 10) and control (n = 9) group pupils. Experimental group pupils showed statistically significant improvement in emotion regulation outcomes, prosocial and internalizing behaviour, but control group pupils showed decrease in emotion regulation outcomes and increase of internalizing behaviour. Both between-group and within- group analysis indicated, that internalizing behaviour results have most pronounced changes. Repeated measures ANOVA and Post hoc test with Bonferroni adjustment revealed statistically significant time effect for experimental group pupils (F(2,18)=4.81, p=0.02, η2=0.35) and tendency level with 90% probability for control group pupils (F(2,16)=3.40, p=0.06, η2=0.30). Saliva cortisol showed decrease in pre and post levels, in some sessions achieving level of significance.